Towards the development of a model for successful business entrepreneurship in Indonesia - Sundjaja, Ridwan S. (Animo Repository, 1990)
This study aims to evolve a model for successful entrepreneurship in Indonesia. The study utilized the case study to probe deeply and analyse intensively the multifarious phenomena of successful entrepreneurs. The method was inductive and was carried out by systematically examining and comparing different sets of empirical data to answer the research questions. The data and analyses and interpretation of the data were qualitative. Inferences were drawn directly from the qualitative statements and descriptions. The tentative dimensions of personal, family, and enterprise were used for comparative analysis in the case studies of successful entrepreneurship. Respondents of the study were five out of 25 successful entrepreneurs from top 40 successful private enterprises who meet the criteria of small-scale family business, initial support from family, present annual sales volume of Rp. 400 billion, and total assets of Rp. 200 billion. Respondents were interviewed based on an interview guide. Interviews were audio-recorded, transcribed and content analyzed. Based on the findings of the study, the following conclusions were made: 1. Successful entrepreneurs generally come from the families who are engaged in business undertakings. 2. Entrepreneurial success in Indonesia may be related with the personal dimensions of hardwork, ability to take calculated risk, flexibility, foresight, and profit. 3. The presence of opportunities, entrepreneurs' personal network, politics and the economy may also influence entrepreneurial success. 4. Successful enterprises in Indonesia go through particular stages of development.